Niveles de metales pesados en los sedimentos superficiales de las zonas de playas turísticas de La Guajira, Norte de Colombia (2018)
Heavy metals (Cr,Cd,V,Zn,Pb,Ni,Hg,Cu) were determined in surface sediments in six sites of the tourist beaches of la Guajira to establish baseline and contamination levels, The metals were determined by means of the atomic absorption technique (CVAAS, GFAAS, FLAAS) using an ICE 3000 Thermo Electron Corporation spectrophotometer with air-acetylene flame. The concentrations of heavy metals in the sediments of the study area varied: Cr, 0.086- 1,058 mg/kg; Cd, 0.00098-0.0002.84 mg/kg; V,0.046-0,829mg/kg; Zn,0.250-0,630 mg/kg; Pb,0.055-0.124 µg/kg; Ni, 0.080-1.220 mg/kg; Hg, 0.0015-0.0027 mg/kg, and Cu,0.030-0.10 mg/kg. Statistically significant correlations between metals suggest sources of similar origins. The estimation of the level of contamination by means of the Geoaccumulation Index indicates that there is no marine pollution. The concentrations of Cr, Zn and Ni They are below a level of light pollution in the sediments, which can be tolerated by most benthic species, although the anthropogenic contribution related to the dumping of wastewater, mining and the discharge of wastewater can not be ruled out.